2021
DOI: 10.1038/s41385-020-00350-x
|View full text |Cite
|
Sign up to set email alerts
|

B cells and the microbiota: a missing connection in food allergy

Abstract: Food allergies are a major public health concern due to their widespread and rising prevalence. The increase in food allergy is partially due to Western lifestyle habits which deplete protective commensal microbiota. These microbial perturbations can result in adverse host-microbe interactions, altering the phenotype of various immune cells and instigating allergic sensitization. Although B cells are critical to allergic pathology, microbial influences on B cells have been somewhat overlooked. Here, we focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 145 publications
(198 reference statements)
1
15
0
Order By: Relevance
“…and (3) IgA production, an essential component of mucosal immune defense. Bacterial-derived antigens and short-chain fatty acids directly interact with B cells to induce IgA production through G-protein coupled receptors signaling, and possibly act indirectly through intestinal epithelial cells or dendritic cells in T-cell-dependent and -independent pathways ( 99 ). However, other studies reported conflicting results.…”
Section: Probiotic Interventionmentioning
confidence: 99%
“…and (3) IgA production, an essential component of mucosal immune defense. Bacterial-derived antigens and short-chain fatty acids directly interact with B cells to induce IgA production through G-protein coupled receptors signaling, and possibly act indirectly through intestinal epithelial cells or dendritic cells in T-cell-dependent and -independent pathways ( 99 ). However, other studies reported conflicting results.…”
Section: Probiotic Interventionmentioning
confidence: 99%
“…Commensal microorganisms modulate B cells to produce various cytokines for maintaining homeostasis or promoting inflammation 73 . Bregs can be induced by intestinal microbiota to produce IL‐10 to combat arthritis in mice 62 .…”
Section: Microbiota and B‐cell Functionmentioning
confidence: 99%
“…Commensal microorganisms modulate B cells to produce various cytokines for maintaining homeostasis or promoting inflammation. 73 Bregs can be induced by intestinal microbiota to produce IL-10 to combat arthritis in mice. 62 Moreover, the microbial metabolite butyrate has the potential to attenuate arthritis severity by triggering Breg-producing IL-10 production while inhibiting GC and plasma cell formation.…”
Section: Cytokine Productionmentioning
confidence: 99%
“…Furthermore CD4 + Foxp3 + Treg and CD8 + Foxp3 + Treg cooperate to limit allergic symptoms via IL-10 secretion during allergen immunotherapy ( 7 ). Regulatory B cells (Breg) regulate immune responses by suppressing effector T cells through the production of anti-inflammatory cytokines (IL-10 and TGF-β) ( 8 ). In mice, IL-10-secreting Breg decrease anaphylaxis following a challenge with cow’s milk allergens through the induction of CD4 + Foxp3 + Treg ( 9 ).…”
Section: Introductionmentioning
confidence: 99%